2003
DOI: 10.1183/09031936.03.00406003
|View full text |Cite
|
Sign up to set email alerts
|

Screening

Abstract: Screening for cancer is currently entering a very promising period as new technologies become available for assessment. However, this great opportunity also presents significant problems, starting with how do you select the likeliest method for evaluation? How do you do trials where the technology will be out-moded by the time the result is known? Indeed, how can all promising technologies be evaluated?There is a need for a renewal of methodological thinking on this topic at present. Randomised trials, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…This pattern is relatively recent and can be attributed to the screening programs (1,5,6), which have been introduced over 50 years (7)(8)(9). Cytological Papanicolaou (Pap) smear screening remains the best method readily available in reducing the incidence and mortality of CC (10). Various studies (mainly time series and case-control) revealed that widespread use of cervical screening in developed societies has been associated with the substantial reduction in the incidence rate of and mortality from CC (1,3,5,7,(11)(12)(13)(14)(15)(16)(17)(18)(19), including Japan (14,18).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is relatively recent and can be attributed to the screening programs (1,5,6), which have been introduced over 50 years (7)(8)(9). Cytological Papanicolaou (Pap) smear screening remains the best method readily available in reducing the incidence and mortality of CC (10). Various studies (mainly time series and case-control) revealed that widespread use of cervical screening in developed societies has been associated with the substantial reduction in the incidence rate of and mortality from CC (1,3,5,7,(11)(12)(13)(14)(15)(16)(17)(18)(19), including Japan (14,18).…”
Section: Introductionmentioning
confidence: 99%
“…It begins with an overview of the general principles of screening and early detection by BOYLE [18]. Early detection of asthma and COPD in general practice is then addressed by VAN SCHAYCK and CHAVANNES [8].…”
mentioning
confidence: 99%